Pengembangan Teknologi E-Marketplace Jasa Penjahit di KOTIM dengan Metode SMART dan Location Based Services - Atiaini, Cicilia Elfrida; Mustaqiem, Mustaqiem; Minarni, Minarni (TIN: Terapan Informatika Nusantara, 2022)
The rapid development of technology can make things easier, faster and more comfortable. The use of technology itself does not only benefit one party but also all parties, indirectly we must follow technological developments so that we can be superior to others. And with the virtual world created because of the development of internet technology, it is what indirectly creates a separate market or trading platform which is now commonly referred to as an e-marketplace. As the market in its conventional sense, which is a place where sellers and buyers meet directly, while in e-marketplaces, sellers and buyers meet in cyberspace and are not limited by space or time. This research was conducted using the SMART method and Location Based Services. Data collection techniques were carried out by means of observation and literature study. From the results of the research on the Development of E-Marketplace Technology for Tailor Services in Kotim with the SMART method and Location Based Services, this is an e-marketplace for tailor services for tailor service providers to market or sell their services in the Kotim area, the program created can be used for tailor service users. in finding a tailor's location, and the program created can also be used for tailor service users in determining which tailor to choose based on several assessments of the existing tailor criteria